Kandungan HCN, Protein Kasar dan Lemak Kasar Tepung Biji Durian Fermentasi dengan Inokulum EM4 - Suhaemi, Zasmeli (Jurnal Embrio, 2009)
In this study, we aim to examine the effect of fermentation of Durian seed meal by Effective Miroorganisms-4 (EM4). To increase protein content and decrease HCN content of Durian seed, we trait to fermented it by EM4 6% with various long fermentation time (3, 4, 5 and 6 days) as the treatment A, B, C and D. Its used Completed Randomized Design 4 X 4 replications. The variables used in this study included HCN, Crude Protein and Crude Fat content. The result showed that not significantly found on HCN and Crude Fat content, but highly significant on Crude Protein content. The best result was on durian seed meal fermented with 5 days long fermentation. The Crude Protein content raise from 3,85% to 12,22%, and HCN content decrease from 80,85 ppm to 16,62 ppm, also Crude Fat content decrease from 8,61% to 0,62%.